Method for testing rolling contact fatigue of steel rail
By simulating abrasions with laser engraving on the surface of rail test specimens and combining this with ultrasonic cleaning and rolling contact fatigue testing, the problem of the inability to evaluate the impact of abrasions in existing technologies has been solved, and an accurate assessment of the rolling contact fatigue performance of rails has been achieved.
Patent Information
- Application Number
- CN202511522283.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-23
- Publication Date
- 2026-01-23
AI Technical Summary
Existing technologies cannot accurately evaluate the impact of abrasion on the rolling contact fatigue performance of rails, especially under the multivariate coupling effect of different abrasion shapes and depths, which makes the evaluation quite difficult.
Laser engraving was used to simulate scratches of different shapes and depths on the surface of the test sample. Combined with ultrasonic cleaning and rolling contact fatigue testing, the test was conducted in a double-disc rolling manner, and vibration signals and weight changes were recorded to evaluate fatigue performance.
It can more accurately evaluate the rolling contact fatigue performance of rails under bruising conditions, simulate actual train operating conditions, and provide a more realistic fatigue wear assessment.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of rail test, in particular to a test method for rolling contact fatigue of rail. BACKGROUND
[0002] Rail is a key component for bearing train operation. In the process of repeated rolling of train wheel, rail and wheel gradually adapt to each other, and smooth contact light bands are formed on the surfaces of rail and wheel. Under normal circumstances, the contact light band is flat and smooth, and the wheel and the rail fit well on the contact light band. However, due to wind and sand, mountain stone falling, missing of construction parts and other conditions, foreign matters of various shapes and materials may occasionally appear on the surface of the rail. When the train passes, the foreign matters are pressed into the surface of the rail to form jam injuries of different shapes and depths. The jam injuries will destroy the wheel-rail contact state, and stress concentration and impact will occur at the jam injury position when the train passes, which will cause cracks, rolling contact fatigue damage and metal spalling, and even may cause rail fracture. It seriously affects the smoothness and safety of train operation.
[0003] The existing standard method for evaluating the rolling contact fatigue performance of metal materials is YB / T 5345-2014 Metal Material Rolling Contact Fatigue Test Method. According to the requirements, the metal material is processed into a disc sample with a diameter of 60 mm, and the rolling contact fatigue test is carried out by double-disc rolling. The surface of the sample is required to be smooth, and the surface smoothness should reach △0.2.
[0004] Using the existing test method, only the rolling contact fatigue performance of the rail material itself under normal wheel-rail contact conditions can be evaluated. The influence of jam injury on the rolling contact fatigue performance of the rail is difficult to evaluate, especially under the coupling action of different jam injury shapes and jam injury depths.
[0005] Therefore, a test method for more accurately evaluating the rolling contact fatigue performance of the rail under jam injury conditions is needed. SUMMARY
[0006] Therefore, the purpose of the present application is to provide a test method for rolling contact fatigue of rail, which can accurately evaluate the rolling contact fatigue performance of the rail under different jam injury conditions.
[0007] The present application provides a test method for rolling contact fatigue of rail, comprising the following steps:
[0008] (1) preparing a test sample and a companion grinding sample;
[0009] (2) simulating the jam injury of the required shape and depth on the test sample by laser marking;
[0010] (3) completely immerse the test sample prepared in steps (1) and (2) and the grinding sample in step (1) in anhydrous ethanol, take out after ultrasonic cleaning, and record the weight after the anhydrous ethanol is completely volatilized;
[0011] (4) perform a rolling contact fatigue test on the test sample prepared in steps (1), (2) and (3) and the grinding sample in step (1), the rotating speed is 0-2000 rpm, and the loading load is 0-20000 N; after the test reaches the required test cycles, stop the test, record the vibration signal, and take out the test sample and the grinding sample;
[0012] (5) completely immerse the test sample obtained in step (4) in anhydrous ethanol, take out after ultrasonic cleaning, and record the weight again after the anhydrous ethanol is completely volatilized;
[0013] (6) subtract the weight of the test sample recorded in step (5) from the weight of the test sample recorded in step (3) to obtain the weight loss of the test sample;
[0014] (7) observe the surface contact fatigue damage of the test samples in steps (4) and (5) by means of tools, and record.
[0015] Preferably, the power of the laser marking is 20-100 W.
[0016] Preferably, the smoothness of the test sample and the grinding sample is △0.2.
[0017] Preferably, the test sample is laser marked with different shapes and different depths in step (2).
[0018] Preferably, the laser marking of the test sample is of a required shape, and the depth is 0.1-2.0 mm.
[0019] Preferably, the loading load is 4000-20000 N.
[0020] Preferably, the rotating speed of the test sample is 200-1000 rpm, and the rotating speed of the grinding sample is (the rotating speed of the test sample x 1.005-the rotating speed of the test sample x 1.030) rpm.
[0021] Preferably, the test cycles in step (4) are 20000-100000 times.
[0022] Preferably, the diameter of the test sample is 60 mm, and the diameter of the grinding sample is 60 mm.
[0023] Preferably, the test sample and the grinding sample both adopt U75VH 60KG / m.
[0024] The application provides a rolling contact fatigue test method for a rail material, which can evaluate the contact fatigue performance of rails of multiple steel types in the presence of a galling situation, can adjust the size, shape and depth of laser marking according to actual needs, is suitable for test evaluation of rails in various service conditions such as high-speed, heavy-load and general-speed railways, and has a good application prospect. BRIEF DESCRIPTION OF DRAWINGS
[0025] Figure 1 The laser marking on the surface of the test sample in the embodiment of the application is shown in the figure.
[0026] Figure 2 The double-disc and roller contact fatigue test of the application is shown in the figure.
[0027] Figure 3 The test sample in the embodiment 1 of the application is taken from a rail head.
[0028] Figure 4 The schematic diagram of the test sample in the embodiment 1 of the application is shown in the figure. DETAILED DESCRIPTION
[0029] The application provides a test method for rolling contact fatigue of a rail, which comprises the following steps:
[0030] (1) preparing a test sample and a test sample for grinding;
[0031] (2) simulating galling in the required shape and depth on the test sample by laser marking;
[0032] (3) completely immersing the test sample prepared in steps (1) and (2) and the test sample for grinding in step (1) in anhydrous ethanol, taking out after ultrasonic cleaning, weighing and recording after the anhydrous ethanol is completely volatilized;
[0033] (4) performing a rolling contact fatigue test on the test sample prepared in steps (1), (2) and (3) and the test sample for grinding in step (1), the rotating speed is 0-2000 rpm, and the loading load is 0-20000 N; after the test reaches the required test cycle, the test is stopped, the vibration signal is recorded, and the test sample and the test sample for grinding are taken out;
[0034] (5) completely immersing the test sample obtained in step (4) in anhydrous ethanol, taking out after ultrasonic cleaning, weighing and recording again after the anhydrous ethanol is completely volatilized;
[0035] (6) subtracting the weight of the test sample recorded in step (5) from the weight of the test sample recorded in step (3) to obtain the weight loss of the test sample;
[0036] (7) observing the surface contact fatigue damage of the test samples in steps (4) and (5) by means of a tool and recording.
[0037] The test sample and the accompanying grinding sample are prepared; the number of the test sample and the number of the accompanying grinding sample are preferably 1:1; in specific embodiments, the number of the test sample and the number of the accompanying grinding sample are both 4 pieces. The test sample is processed for rolling contact fatigue test of the rail head; in specific embodiments, the diameter of the test sample is 60 mm; according to actual needs, the counter-rolling accompanying grinding sample is processed, and the diameter of the accompanying grinding sample is 60 mm. The surface finish of the test sample and the accompanying grinding sample in the application should reach △0.2, which aims to prevent the test sample surface from being too rough and affecting the test results if the surface finish is less than △0.2, and to prevent the processing difficulty from being increased and the test results from being not obviously affected by the too high surface finish.
[0038] The test method provided by the application simulates the required shape and depth of the test sample by laser marking. Figure 1 The test sample is laser marked with different shapes and depths; preferably, the required shape is a triangle or a circle, and the depth is 0.1-2.0 mm; the depth can be 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, or 2.0 mm. Specifically, the test sample is laser marked with a circular mark with a depth of 0.2 mm, or the test sample is laser marked with a triangular mark with a depth of 0.5 mm, or the test sample is laser marked with a triangular mark with a depth of 0.2 mm. The laser marking machine has adjustable focal length and adjustable laser power; meanwhile, the laser marking machine should be equipped with software that can import and edit various marking shapes; the rolling contact fatigue test machine for carrying out double-disc counter-rolling test should be able to realize double-wheel stepless speed change; the rolling contact fatigue test machine should be able to realize stepless speed loading; meanwhile, the fatigue test machine should have vibration signal acquisition function.
[0039] The focal length of the laser marking machine used in the application is adjustable, which aims to prepare markings with different depths; the laser power of the laser marking machine used is adjustable, and the marking laser power should be 20-100 W, which aims to quickly and effectively prepare the markings; if the laser efficiency is less than 20 W, the marking efficiency is too low; if the laser efficiency is greater than 100 W, the power is too high, which is easy to cause the test sample surface to be over-burned and affect the marking quality; the laser marking machine used should be equipped with software that can import and edit various marking shapes, which aims to be able to mark various shapes, and be more in line with the actual situation.
[0040] The test sample prepared through steps (1) and (2) and the grinding sample of step (1) are completely immersed in anhydrous ethanol, taken out after ultrasonic cleaning, and weighed and recorded after the anhydrous ethanol is completely volatilized.
[0041] The test sample prepared through steps (1), (2) and (3) and the grinding sample of step (1) are subjected to rolling contact fatigue test, the rotating speed is 0-2000 rpm, and the loading load is 0-20000 N; after the test reaches the required test cycle, the test is stopped, the vibration signal is recorded, and the test sample and the grinding sample are removed. Figure 2 The test load, the rotating speed of the test sample and the grinding sample, and the total test cycle are set according to the test requirements. The rolling contact fatigue testing machine used should be capable of double-wheel stepless speed change, and the rotating speed should satisfy 0-2000 rpm, which aims to simulate the relative sliding of the line rail and the wheel, and is more in line with the actual situation, and the rotating speed of 0-2000 rpm can satisfy the simulation of the existing train speed requirement; if the rotating speed is greater than 2000 rpm, the test temperature is too high, which affects the test result; the rolling contact fatigue testing machine used should be capable of stepless speed change loading, and the loading load is 0-20000 N, which aims to 0-20000 N load, which can satisfy the simulation of the existing train weight requirement, and is preferably 4000-20000 N; if the loading load is greater than 20000 N, the test torque is too large, the test temperature is too high, and the test result is affected; preferably, the rotating speed of the test sample is 200-1000 rpm, and the rotating speed of the grinding sample is (the rotating speed of the test sample x 1.005-the rotating speed of the test sample x 1.030) rpm. The rolling contact fatigue testing machine used should have a vibration signal collection function, which aims to use the vibration signal to evaluate the damage of the rail surface. After the test reaches the required test cycle, the test is stopped, the vibration signal is recorded, and the test sample and the grinding sample are removed. The test cycle is 20000-100000 times, and is preferably 50000 times. In the specific embodiment, the loading load is 4000 N, the rotating speed of the test sample is 500 rpm, the rotating speed of the grinding sample is 505 rpm, and the test cycle is 50000 times.
[0042] The test sample obtained in step (4) is completely immersed in anhydrous ethanol, taken out after ultrasonic cleaning, and weighed and recorded again after the anhydrous ethanol is completely volatilized.
[0043] The weight loss of the test sample is obtained by subtracting the weight of the test sample recorded in step (5) from the weight of the test sample recorded in step (3).
[0044] The surface contact fatigue damage of the test sample of steps (4) and (5) is observed by means of a tool, and is recorded.
[0045] The rolling contact fatigue test method provided by the application processes a rolling contact fatigue test sample on a rail head according to test requirements; and processes a rolling contact fatigue test sample according to requirements; uses a laser marking machine to mark a required shape and depth on the surface of the processed rolling contact fatigue test sample to simulate a chipping injury; uses anhydrous ethanol to clean the test sample and the grinding sample in an ultrasonic cleaner, and weighs and records the test sample and the grinding sample after drying. The rolling contact fatigue test is carried out on a rolling contact fatigue test machine, and the test load, the test sample and the grinding sample speed, and the total test cycle are set according to the test requirements; after the test reaches the required test cycle, the test is stopped, the vibration signal is recorded, and the test sample and the grinding sample are removed; the test sample is cleaned in an ultrasonic cleaner using anhydrous ethanol, and weighed and recorded after drying. The weight loss is obtained by subtracting the weight after the test from the weight before the test. The surface contact fatigue damage of the test sample is observed using a microscope, and the observation results are recorded.
[0046] In order to further illustrate the application, the test method for the rolling contact fatigue of a rail provided by the application is described in detail below in combination with examples, but they should not be understood as limiting the protection scope of the application.
[0047] Example 1
[0048] One U75VH 60kg / m rail is selected to process four rolling contact fatigue test samples, and the processing position and size are as shown in Figure 3 Four grinding samples are processed at the same time, and the sample size is as shown in Figure 4
[0049] Three rolling contact fatigue test samples are randomly selected, and a 0.2mm deep circular marking, a 0.2mm deep triangular marking and a 0.5mm deep triangular marking are respectively prepared on the surface of the test samples according to the method described in the application. The rolling contact fatigue test is carried out according to the method described in the application, and the test results are recorded as examples. One rolling contact fatigue test sample is randomly selected, and no chipping injury simulation is performed on the surface, the rolling contact fatigue test is carried out according to the method described in the application, and the test results are recorded as comparative examples.
[0050] The test parameters of the examples and comparative examples are shown in Table 1.
[0051] Table 1
[0052]
[0053] The test results of the examples and the comparative examples are shown in Table 2. When the material of the test sample and the grinding sample, the test load, the test sample rotation speed, the grinding sample rotation speed, and the test cycle are the same, the test results are related to the notch shape and the notch depth. In the examples, when the notch is a 0.2 mm circle, the maximum vibration signal is 1.3 mm / s, the test sample weight loss is 0.3 g, and there are obvious fatigue cracks on the notch circumference. When the notch is a 0.2 mm triangle, the test sample weight loss is 0.49 g, and the fatigue is obvious at the triangle sharp corner position of the notch, and there is slight metal spalling. When the notch is a 0.5 mm triangle, the test sample weight loss is 0.97 g, the fatigue is obvious at the triangle sharp corner position of the notch, and there is a large amount of metal spalling. The notch depth and shape have obvious effects on the test results. When the test sample surface is not notched by using the conventional test method, the vibration signal is stable, the maximum is only 0.2 mm / s, the test sample weight loss is 0.11 g, and there are uniform and slight fatigue cracks on the whole contact band, and the rolling fatigue wear under the rail bruise condition cannot be simulated.
[0054] This indicates that the rolling contact fatigue test method for rail material provided by the present application can more accurately and more truly reflect the effects of the bruise depth and shape on the rolling contact fatigue performance of the rail.
[0055] Table 2 Test results of the examples and the comparative examples
[0056]
[0057] As can be seen from the above examples, the rolling contact fatigue test method for rail material provided by the present application can more accurately evaluate the service performance of the rail under the condition that there is a rail bruise on the rail surface, and is very suitable for carrying out the service performance research of the rail.
[0058] The above only describes the preferred embodiments of the present application, and it should be noted that, for those skilled in the art, without departing from the principles of the present application, a number of improvements and refinements can be made, and these improvements and refinements should also be considered as the protection scope of the present application.
Claims
1. A test method for rolling contact fatigue of steel rails, comprising the following steps: (1) Preparation of test samples and grinding samples; (2) The test sample is subjected to simulated dents of the required shape and depth using laser engraving; (3) The test sample prepared in steps (1) and (2) and the sample prepared in step (1) are completely immersed in anhydrous ethanol, ultrasonically cleaned and taken out. After the anhydrous ethanol has evaporated, weigh and record the results. (4) The test specimens prepared in steps (1), (2) and (3) and the grinding sample in step (1) are subjected to rolling contact fatigue test. The rotation speed is 0~2000 rpm and the load is 0~20000 N. After the test reaches the required number of test cycles, the test is stopped, the vibration signal is recorded, and the test specimens and grinding samples are removed. (5) Immerse the test sample obtained in step (4) completely in anhydrous ethanol, clean it with ultrasonication, take it out, wait for the anhydrous ethanol to evaporate completely, weigh it again, and record the result. (6) Subtract the weight of the test sample recorded in step (5) from the weight of the test sample recorded in step (3) to obtain the weight loss of the test sample; (7) Use tools to observe and record the surface contact fatigue damage of the test specimens in steps (4) and (5).
2. The test method according to claim 1, characterized in that, The power of the laser engraving is 20~100W.
3. The test method according to claim 1, characterized in that, The surface finish of the test sample and the sample being polished was ▽0.
2.
4. The test method according to claim 1, characterized in that, In step (2), the test sample is laser-etched with different shapes and depths.
5. The test method according to claim 1, characterized in that, The test sample was laser-etched into the desired shape with a depth of 0.1~2.0 mm.
6. The test method according to claim 1, characterized in that, The load is 4000~20000N.
7. The test method according to claim 1, characterized in that, The rotation speed of the test sample is 200~1000 rpm, and the rotation speed of the surcharge sample is (test sample rotation speed × 1.005~test sample rotation speed × 1.030) rpm.
8. The test method according to claim 1, characterized in that, The number of test cycles in step (4) is 20,000 to 100,000.
9. The test method according to claim 1, characterized in that, The diameter of the test sample is 60 mm, and the diameter of the grinding sample is 60 mm.
10. The test method according to claim 1, characterized in that, Both the test sample and the grinding sample used were U75VH60KG / m.